In the name of integrality and living in harmony: Genealogy of student counseling departments in Ecuador - Diego Palacios Díaz; Felipe Hidalgo Kawada (Education Policy Analysis Archives, 2021)
In this paper, we analyze from genealogy the emergency of the student counseling department (DECE) in the contemporary educational policies in Ecuador. Specifically, we examine the construction of a new legal–normative architecture from the principles of living in harmony (buen vivir) that seeks to guarantee the delivery of psychological and social services to Ecuadorian students from a novel incorporation of knowledges, practices and expertise based on the psychological sciences. Methodologically, we followed Michel Foucault's principles of genealogy to analyze a textual corpus made up of legal, normative and regulatory documents, as well as interviews with policymakers and district coordinators who participated in the development and implementation processes of educational policies related to DECE. Thus, through our axes of analysis we expose the configuration of a new State rationality around the notion of integrality, and through a variety of sociotechnical, regulatory and practical adjustments, the promotion of  management logics focused on governing and controlling specific forms in which professionals deploy their actions in schools. Finally, we discuss how the Sumak Kawsay knowledges are relegated, compared to an influential scientific-technical rationale that seeks to orientate educational processes in specific ways with a psychological language based on biomedical perspectives that inhibit alternative ways of understanding the subject and subjectivity within Ecuadorian education.